Longitudinal perspectives on crowding and management at a beach park in Hawai'i. (1st October 2021) - Szuster, Brian W.; Peng, Marcus
Abstract: This research adds to a small body of literature studying longitudinal change in coastal tourism environments. Site use and crowding at Kailua Beach Park in Hawai'i was investigated through research conducted in 2007 and 2019. Reported encounters, perceived crowding and the minimum acceptable condition all increased between these years. Overall, crowding scores were highest for respondents who reported more encounters than they think should be allowed, and the percentage of users who encountered more people than they think should be allowed has grown substantially. A significant increase of US mainland users was identified in 2019 (which mirrors broader tourism trends in Hawai'i) and local beach users are now in the minority at this site. Respondents from the USA mainland were less likely than local or international user groups to experience encounters exceeding their norm, and if their encounter norms were exceeded, USA mainland respondents generally displayed lower crowding scores. These findings have implications for norm stability, the development of appropriate standards of quality for crowding, and post-pandemic management. Highlights: Only a small number of longitudinal studies have been completed in coastal tourism environments. Encounters, crowding and the minimum acceptable condition all increased between 2007 and 2019. Norms and crowding at Kailua Beach Park are now influenced residency of users. Findings have implications for norm stability, crowding standards and post-pandemic management.